Pengembangan Media Dakpin Materi Konsep FPB dan KPK pada Siswa Kelas IV MI Tarbiyatul Banin - Eksa Zanuar Aris Sagita; Iqnatia Alfiansyah; Arissona Dia Indah Sari (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to (1) describe the development of Dakpin media for learning the concepts of Greatest Common Factor (GCF) and Least Common Multiple (LCM) for fourth-grade students at MI Tarbiyatul Banin, and (2) determine the validity of the developed media. The research employed the ADDIE development model, consisting of Analyze, Design, Develop, Implement, and Evaluate stages. The study was conducted at MI Tarbiyatul Banin during the first semester, involving 11 fourth-grade students as research subjects. Data were collected through material and media expert validation questionnaires, student response questionnaires, tests, observations, and interviews. The results indicate that the Dakpin media was successfully developed through all stages of the ADDIE model and was considered highly valid for use in mathematics learning. Validation results showed an average score of 93.75% from material experts and 94.79% from media experts, both categorized as “very valid.” In addition, student responses toward the use of Dakpin media reached 91%, indicating a highly positive reception. These findings suggest that Dakpin media is appropriate and effective as a learning tool to support students’ understanding of GCF and LCM concepts in elementary mathematics learning.